Stimulation Techniques of Coalbed Methane Reservoirs. (10th July 2020) - Zhang, Jicheng; Si, Leilei; Chen, Junguo; Kizil, Mehmet; Wang, Chunguang; Chen, Zhongwei
Abstract : Coalbed methane (CBM) plays an important role in securing world energy supply and transiting electricity generation from fossil fuel to renewables. CBM reservoirs are generally very tight and require effective stimulation to achieve economic extraction. In recent years, an increasing number of coal seam stimulation techniques were developed, but selecting the most suitable stimulation technique for a particular CBM reservoir condition is becoming increasingly challenging. Therefore, it is deemed very important to compare the effectiveness of different stimulation techniques in a meaningful way to guide future research directions in this area. In this paper, the stimulation techniques were firstly classified into different categories according to the stimulation mechanisms. Then, the associated principles, the history of advances, and challenges of different stimulation techniques were comprehensively reviewed. Two indexes were proposed to compare the stimulation effectiveness at the laboratory and field scales, respectively. Finally, the comparison and evaluation of each stimulation technique in respect to the stimulation effectiveness, influence range, duration, and environment were conducted in detail; the cryogenic liquid nitrogen stimulation technique receives the highest total score among the discussed laboratory-scale stimulation techniques. Hydraulic fracturing and gas injection stimulation techniques gain the highest total score among key field-scale stimulation techniques. Considering the time required for each stimulation method to take effect, high-voltage electric fracturing may have a greater potential in the future. This work is expected to help better select the optimal stimulation technique for reservoir specific conditions.